The Effect of Cobalt Dopant on Structural and Optical Properties of Tin Sulfide Thin Films (Journal of the College of Basic Education, 2022)
SnS and SnS: Co thin films wad deposit by chemical spray pyrolysis (CSP) method on 450C heated glass substrates. XRD study revealed that the films all films are polycrystalline diffraction, and the predominant peak was (111) plane. The grain size of SnS and doped SnS: 3 % Co is 19.07 nm and 21.58 nm, respectively, whereas the strain (%) parameter decreases 18.17 to 16.06. The produced film has a transparency of about 85%, which declines as the doping concentration increases. The optical band gap reduced from 1.57 eV for SnS thin film to 1.45 eV for 3 % Co doped Tin sulfide film. The absorption coefficient (α) increases with Cobalt content, whilst the extinction coefficient and refractive Index have decreased with Cobalt content in Tin sulfide thin films.